Exchange Rate Arrangements and Monetary Policy. (IMF Working Papers; Working Paper ;, 1988)
This paper examines the relationship between monetary and exchange rate policies by considering the factors that have led the authorities in developed and developing countries in Asia to alter their use of monetary policy instruments and exchange rate arrangements since the mid-1970s. There is first consideration of the extent to which real and monetary shocks, country size, and the degree of goods and capital market integration can explain the evolution of exchange rate arrangements. There is then an examination of the factors influencing the choice of money and credit policy instruments. Finally, there is a discussion of integrating monetary and exchange policies with extensive trade and financial market reforms.